2000
DOI: 10.1046/j.1365-313x.2000.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome analysis reveals extensive conservation of genome organisation for Arabidopsis thaliana and Capsella rubella

Abstract: SummaryGenome colinearity has been studied for two closely related diploid species of the Brassicaceae family, Arabidopsis thaliana and Capsella rubella. Markers mapping to chromosome 4 of A. thaliana were found on two linkage groups in Capsella and colinear segments spanning more than 10 cM were revealed. Detailed analysis of a 60 kbp region in A. thaliana and its counterpart in C. rubella showed virtually complete conservation of gene repertoire, order and orientation. The comparison of orthologous genes rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 30 publications
4
54
1
Order By: Relevance
“…The lineages of Brassica and Arabidopsis/Capsella were estimated to have separated approximately 12.2-19.5 million years ago, whereas for Arabidopsis and Capsella, the estimate is of 6.2-9.8 million years (Acarkan et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lineages of Brassica and Arabidopsis/Capsella were estimated to have separated approximately 12.2-19.5 million years ago, whereas for Arabidopsis and Capsella, the estimate is of 6.2-9.8 million years (Acarkan et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Capsella appears to be closely related to Arabidopsis (Koch et al, , 2001 on the basis of sequence data from various nuclear genes and cpDNA. Comparative genome analysis has revealed extensive conservation of genome organisation among Arabidopsis thaliana and C. rubella (Acarkan et al, 2000;Koch and Kiefer, 2005). Owing to this close relationship it should be possible to make use of the present knowledge of Arabidopsis SI in research on Capsella.…”
Section: The Genus Capsellamentioning
confidence: 99%
“…Comparing the genetic maps of Arabidopsis and different Brassica species also has revealed many colinear chromosome segments for species belonging to the Brassicaceae family (reviewed in Schmidt, 2000). The results of the first microsynteny studies using sequencelevel resolution in the Poaceae (Chen et al, 1997;Messing and Llaca, 1998;Tikhonov et al, 1999) and Brassicaceae families (Grant et al, 1998;Acarkan et al, 2000) support the view that genome colinearity can be observed at the level of genes.…”
Section: Introductionmentioning
confidence: 77%
“…Comparing the genetic maps of Arabidopsis and different Brassica species also has revealed many colinear chromosome segments for species belonging to the Brassicaceae family (reviewed in Schmidt, 2000). The results of the first microsynteny studies using sequencelevel resolution in the Poaceae (Chen et al, 1997;Messing and Llaca, 1998;Tikhonov et al, 1999) and Brassicaceae families (Grant et al, 1998;Acarkan et al, 2000) support the view that genome colinearity can be observed at the level of genes.Few attempts to analyze genome colinearity between more distantly related species have been reported (Paterson et al, 1996;Devos et al, 1999;van Dodeweerd et al, 1999;Ku et al, 2000). The low degree of sequence homology in distantly related species hampers the unambiguous 1 These authors contributed equally to this work.…”
mentioning
confidence: 77%
“…Until now, it was thought that transfer of SI would be limited to close relatives, as so far the only movement of SI systems has been within species or closely related species, Arabidopsis lyrata and Capsella grandifl ora into A. thaliana (Nasrallah et al 2002 ;Boggs et al 2009 ). Although these are important demonstrations, they diverged only ~5 million , and ~6.2-9.8 million years ago (Acarkan et al 2000 ), respectively, and so do not provide major insights into the evolution of SI signaling across angiosperm families because of their close relationship and their possession of a mechanistically common SI system. Our fi ndings provide a breakthrough in this area, as transferral of the Papaver pollen S -determinant into A. thaliana is between highly diverged species with ~144 million years separating them (Bell et al 2010 ), and they do not share a common SI system.…”
Section: Recruitment Of Signaling For Si Events In Other Speciesmentioning
confidence: 99%